Species Composition and Control of Plants Which Damage Pineapple Trees in Khorazm Region - Sobirov Asror Rasul o’g’li; Yuvbasarov Hamdam Inoyatovich; Ismayilova Intizar (Zien Journals, 2023)
This article identifies aphid species that are commonly found on arborvitae and juniper trees planted as ornamental trees in the Khorezm region, presents their bioecological characteristics and countermeasures.
Keywords: tree; aphid; insecticide; entomophage